In vitro Comparison of the Microhardness of Lithium Disilicate and Monolithic and Multilayered Fixed Prosthodontic Materials - Milad Elshah,; Asmaa Abdeewi,; Mohamed Zeglam, (AlQalam Journal of Medical and Applied Sciences, 2025)
Micro-hardness is a fundamental property of prosthodontic restorative materials, as it affects their resistance to surface deformation, wear, and long-term clinical performance. This study aimed to compare the Vickers micro-hardness of three widely used CAD/CAM materials: lithium disilicate, monolithic zirconia, and multilayered zirconia. A total of 30 specimens (N = 30) were fabricated, with 10 samples allocated to each material group. Lithium disilicate specimens were prepared as rectangular plates (18 × 15 × 1 mm), whereas zirconia specimens—both monolithic and multilayered—were fabricated as discs (10 mm in diameter and 1.5 mm in thickness) following standardized CAD/CAM milling and sintering protocols. Vickers micro-hardness testing was conducted using a digital micro-hardness tester under material-specific conditions: a load of 1 kg and a dwell time of 10 s for lithium disilicate, and a load of 500 g with a 20 s dwell time for zirconia. Statistical analysis was performed using one-way ANOVA followed by Tukey’s post-hoc test, with the significance level set at p < 0.05. Significant differences in micro-hardness were identified among the three materials (p < 0.001). Monolithic zirconia demonstrated the highest mean hardness (680 ± 19 HV), followed by multilayered zirconia (623 ± 47 HV), while lithium disilicate exhibited the lowest values (553 ± 32 HV). Post-hoc analysis confirmed that all pairwise comparisons were statistically significant. The findings indicate that monolithic zirconia possesses superior micro-hardness compared to multilayered zirconia and lithium disilicate, supporting its suitability for high-stress clinical applications. Multilayered zirconia offers a balance between mechanical performance and esthetics, whereas lithium disilicate remains optimal for highly esthetic anterior restorations. These results provide clinicians with evidence-based guidance for selecting CAD/CAM materials in fixed prosthodontic rehabilitation.